“GESTÃO DA PERDA DE ALIMENTOS NA CADEIA DE HORTIFRÚTI: UMA ANÁLISE NA PERSPECTIVA DA ECONOMIA CIRCULAR” - Naiade Valenzuela de Alcantara (2023)
Most food chains use natural resources in a linear way “extract, produce, discard” (Aznar Sánchez et al., 2020), in this scenario the circular economy emerges as an alternative to sustainable agriculture, that is, a new way to manage natural resources. The European and Chinese governments have adopted measures based on the Circular Economy, through regulations and legislation. In Brazil, the concept and implementation are in the early stages, and research that contributes to these practices is important. Regarding food chains, in this work we will focus on the production of fruit and vegetables, since these products are highly perishable, requiring the adoption of strategies to reduce loss rates. The production of fruit and vegetables in Mato Grosso do Sul is small, generating a low supply of local production, which can lead to food insecurity if the products do not come from other locations. That said, the present study will investigate how the producers of hortifruti from Campo Grande - MS are doing to reduce losses in the chain, from the perspective of principles and practices of Circular Economy. Data were collected through semi-structured interviews and data analysis was performed using categories defined by content analysis (Bardin, 1977). The results showed that producers carry out Circular Economy practices in order to reduce loss and waste in the chain, and that they also have some incremental innovation initiatives. The main contribution of this study is to offer insights for a breakthrough in the implementation of new circular economy practices in the fruit and vegetable production chain. Based on knowledge about the local functioning of fruit and vegetables, it was possible, in addition to identifying the practices used in the sector, to learn about the difficulties faced by fruit and vegetable producers and how they use innovation to overcome these barriers encountered. These difficulties end up directly impacting the implementation of new circular practices and the relationship between producers and their business partners. With this issue, this work also contributes by bringing a series of proposals to help the sector move increasingly towards sustainability through the Circular Economy. Keywords: Circular Economy. Innovation. Hortifruti Production. Food Waste.